Constructing Quasi‐Localized High‐Concentration Solvation Structures to Stabilize Battery Interfaces in Nonflammable Phosphate‐Based Electrolyte - Zari Tehrani (Advanced Science, 2025)
Flame-retardant phosphate-based electrolytes effectively enhance lithium-ion battery safety but suffer from poor compatibility with graphite anodes and high-voltage cathodes, hindering scalability. Fluorinated phosphates, though widely used, increase interfacial resistance at the anode, degrading performance. In this work, carbonate solvents with strong polarity are introduced to prevent tris(2,2,2-trifluoroethyl) phosphate (TFEP) from participating in the solvation structure of lithium ions. This strategy forms a quasi-localized high-concentration solvation structure, thereby restricting the reduction of TFEP and its impact on the graphite anode. The LiNi0.8Mn0.1Co0.1O2 (NCM811) | Graphite (Gr) pouch cell with optimized electrolyte exhibits a capacity retention rate of 80.1% after 370 cycles at 0.5C, which is much more stable than the electrolyte with TFEP-involved solvation structure (capacity retention rate: 47.1% after 300 cycles). The corresponding pouch cell with cut-off voltage to 4.5 V exhibits a capacity retention rate of 82.8% after 125 cycles, significantly outperforming cells employing commercial carbonate electrolytes (capacity retention rate: 56.9% after 125 cycles). Thus, the developed quasi-localized high-concentration solvation structure can effectively stabilize the electrode interface, greatly enhancing the cycling performance of phosphate-based flame-retardant electrolytes.